Causal pathways linking different flavours of ENSO with the Greater Horn of Africa short rains. (28th October 2020) - MacLeod, David; Graham, Richard; O'Reilly, Chris; Otieno, George; Todd, Martin
Abstract: There is a strong association between canonical El Niño and a wet Greater Horn of Africa (GHA) short rains. However, the link with Modoki El Niño events appears to be significantly weaker. In order to understand this, we present an analysis of observational data and idealised climate model experiments. Idealised atmospheric simulations isolate the direct influence of Pacific heating on the GHA and reveal that neither the longitudinal position nor the observed weaker magnitude of Modoki Pacific heating anomalies can explain the difference in teleconnections. The direct effect of canonical or Modoki Pacific heating patterns on the GHA is similar and neither reproduces the structure of the full GHA teleconnection: they both generate a wet‐dry dipole over the GHA instead of large‐scale single‐signed wet anomalies. Our results indicate that the strong canonical ENSO influence on GHA is indirect, mediated through its strong relationship with the Indian Ocean Dipole (IOD). By contrast, Modoki ENSO is uncorrelated with the IOD, resulting in weak teleconnection to GHA. Understanding these differences aids seasonal forecast interpretation, whilst their representation in models is likely a prerequisite for making accurate projections of changes in extremes over the GHA and beyond. Abstract : Different types of ENSO have different impacts on Greater Horn of Africa (GHA) rainfall. We demonstrate that the canonical East Pacific ENSO acts on GHA through its link with the Indian Ocean Dipole (IOD), whilst the Modoki Central Pacific type does not influence the IOD and so has a weaker influence on GHA. Climate model experiments reveal the direct impact of canonical El Niño on GHA is actually a weak wet‐dry dipole, which is overwhelmed when a positive IOD event is active.